(3Yjhf GdeLGdS aj abg eNJda GdePGgHs - (3CHh eMeO YHO GdhgGH Hf Ydj Hf fUQ GdHZOGOj GdbQGaj GdeGdcjs
(3ChdgG (B:s
(3cJGH GdWgGQI eSCdI (B: (3ZSd GdjOjf bHd GdWgGQI efOhH Edjg hdjS HhGLH YfO eGdc hCHi MfjaI hGdChRGYi hGdTGaYi s
(3BNQgG (B:s
(3jfJgi eG ajgG CKfGA cJGH GdbWY ai GdSQbI hBNQ eG ajg (B: (3hbGd CHh MfjaI (B: (3dG jchf ai GdeUQ bWY s
(3HgG CKGQ JbWjYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3NRGfI LGeYI GdbQhjjf HaGS (B(80 / 268) s
Keywords: (3abg GdePGgH GdCNQis